PPAR-γ agonist rosiglitazone reduces autophagy and promotes functional recovery in experimental traumaticspinal cord injury. (22nd May 2017) - Li, Hongpeng; Zhang, Qin; Yang, Xiaohui; Wang, Liping
Highlights: Current study showed an important protective effect of PPAR-γ agonist ROSG on SCI in rat. ROSG decreased the upregulated autophagy-related protein expression due to SCI and promoted functional recovery. Although the molecular mechanisms underlying PPAR-γ agonist-mediated neuronal autophagy remain to be determined, autophagy may be a new target for the treatment of SCI. Abstract: Background: Secondary damage is often more important in determining the functional outcome and provides a practical target for therapeutic intervention. Rosiglitazone (ROSG) is a potent PPAR-γ agonist and has been shown to induce neuroprotection in animal models of spinal cord injury (SCI). However, it is still unclear whether this PPAR-γ agonist can mediate neuronal autophagy after SCI. Methods: SCI was induced by application of vascular clips (force of 24 g) to the dura via a four-level T5–T8 laminectomy. The role of the PPAR-γ agonist ROSG on neuronal autophagy induced by SCI was investigated. Results: The expression of autophagy-related proteins, including microtubule-associated protein 1 light chain 3 type II (LC3-II), beclin-1, and cathepsin D, increased significantly after SCI. ROSG downregulated autophagy-related protein expression and improved the locomotor function after SCI. GW9662 (a PPAR-γ inhibitor) significantly antagonized the effect of ROSG and abolished the protective effect on SCI. Conclusions: Our results clearly demonstrated that the administration of ROSG after SCI reduced autophagy and promoted functional recovery after SCI in rats.